2016
DOI: 10.1186/s12888-016-0721-0
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing reciprocal partner support to prevent perinatal depression and anxiety: a Delphi consensus study

Abstract: BackgroundSystematic reviews have established that partner support protects against perinatal mood problems. It is therefore a key target for interventions designed to prevent maternal and paternal depression and anxiety. Nonetheless, the extant literature is yet to be translated into specific actions that parents can implement. Prevention efforts aiming to facilitate reciprocal partner support within the couple dyad need to provide specific guidance on how partners can support one another to reduce their vuln… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 66 publications
1
29
0
Order By: Relevance
“…In return, support from family members was crucial, especially from their partners. Partner support was a protective factor for the perinatal psychological health of the women, which could reduce the negative maternal evaluation of childbirth [31,32]. On the other hand, the women expressed the need for professional medical support, which was supported by a previous study [33].…”
Section: Discussionmentioning
confidence: 86%
“…In return, support from family members was crucial, especially from their partners. Partner support was a protective factor for the perinatal psychological health of the women, which could reduce the negative maternal evaluation of childbirth [31,32]. On the other hand, the women expressed the need for professional medical support, which was supported by a previous study [33].…”
Section: Discussionmentioning
confidence: 86%
“…Should a Home Visitor identify a father in need of support they are likely to be concerned over the limited number supportive interventions available for fathers with depression and anxiety (O'Brien et al, 2016). Whilst Pilkington et al, (2016) provide some guidelines on how partners can support each other to prevent depression and reduce anxiety during the pregnancy these guidelines take no account of the influence of IPV; a complicating factor for the Health Visitor.…”
Section: Paternal Depressionmentioning
confidence: 99%
“…Many studies have shown that during pregnancy women's mental health is associated with social support [8][9][10], marital relationships [11], as well as socioeconomic factors.…”
Section: Introductionmentioning
confidence: 99%
“…Other studies have also shown that social support, especially the partner's, is of great importance in maintaining the mental health of pregnant women [8,17,18]. Further, affecting the marital relations, the partner's emotional support has important effects on the mental health of women during pregnancy [9,10] in such a way that some studies have reported that the partner's emotional support has a positive relation to increased marital satisfaction in women [19]. However, during pregnancy, among all the partner's supportive behavior, his emotional reaction to pregnancy such as that on learning about his wife's pregnancy or about pregnancyrelated events such as movement of the fetus or the growth of the abdomen as a result of the growth of the fetus, might be of special importance because it indicates the importance of pregnancy to the partner.…”
Section: Introductionmentioning
confidence: 99%